Consumption‐based carbon accounting: does it have a future?. (16th November 2016) - Afionis, Stavros; Sakai, Marco; Scott, Kate; Barrett, John; Gouldson, Andy
Abstract : Internationally, allocation of responsibility for reducing greenhouse gas emissions is currently based on the production‐based (PB) accounting method, which measures emissions generated in the place where goods and services are produced. However, the growth of emissions embodied in trade has raised the question whether we should switch to, or amalgamate PB accounting, with other accounting approaches. Consumption‐based (CB) accounting has so far emerged as the most prominent alternative. This approach accounts for emissions at the point of consumption, attributing all the emissions that occurred in the course of production and distribution to the final consumers of goods and services. This review has a fourfold objective. First, it provides an account of the logic behind attributing responsibility for emissions on the basis of consumption instead of production. Issues of equity and justice, increased emissions coverage, encouragement of cleaner production practices, and political benefits are considered. Second, it discusses the counterarguments, focusing in particular on issues of technical complexity, mitigation effectiveness, and political acceptability. Third, it presents the spectrum of implementation possibilities—ranging from the status quo to more transformative options—and considers the implications for international climate policy that would accrue under various scenarios of adopting CB accounting in practice. Fourth, it looks at how CB accounting may be adjusted to fit with current political realities and it identifies policy mechanisms that could potentially be utilized to directly or indirectly address CB emissions. Such an approach could unlock new opportunities for climate policy innovation and for climate mitigation. WIREs Clim Change 2017, 8:e438. doi: 10.1002/wcc.438 This article is categorized under: Climate Economics > Economics of Mitigation